Autologous grafts in the treatment of avascular osteonecrosis of the femoral head - Marcarelli, Marco; Fiammengo, Marco; Trovato, Letizia; Lancione, Vincenzo; Novarese, Elvio; Indelli, Pier Francesco; Risitano, Salvatore (Acta Biomedica Atenei Parmensis, 2020)
Background: Osteonecrosis of the femoral head (ONFH) is a frequent orthopedic disease leading to destruction of the hip joint and disabling arthritis. Several procedures have been developed to treat the joint deterioration in case of osteonecrosis, trying to avoid or delay an intervention of total hip replacement, especially in young patients. The aim of this study was to analyze the use of autologous bone micrografts derived from cancellous bone in the management of avascular ONFH. The treatment described was implemented using the Rigenera® protocol to obtain autologous micrografts: small fragments of cancellous bone collected by femoral neck, disaggregated and injected in the necrotic area using an empty screw. Materials and methods: Twenty adult patients affected by avascular ONFH were enrolled in this study; all patients reported a preoperative intermittent coxo-arthrosis and limited function of intra and extra rotation of the hip. Inclusion criteria were an Oxford Hip Score between (OHS) 20 and 39, a Harris hip score (HHS) showing pre-operative poor results (lower than 70 points) and a stage II-IIIA and IIIB according with the classification proposed by the Association Research Circulation Osseous (ARCO). Results: Using an MRI evaluation, after six months, the authors observed a complete regression of necrotic area and the restoration of osseous structure. Clinical outcome has been evaluated at 6-12 and 24 months follow-up. At the final F.U. the HHS rised from poor to good results (mean value at final F.U of 84) while the OHS improved significantly already after 21 days from micrografts injection (mean 35.4 ± 7.5) with an increasing trend until to two-year final FU (mean 37.4 ± 9.5). The full recovery of daily and mild sport activities was reached after 20 and 90 days from intervention, respectively. Conclusion: The results of this study are suggestive for a new approach in the treatment of avascular ONFH assuming a process of bone regeneration based on a dual mechanism of action, biological and mechanical, induced by micrografts and injected using an empty screw as vehicle.